Distinct Effects of Dexamethasone on Human Natural Killer Cell Responses Dependent on Cytokines - Morgan, David J.; Davis, Daniel M. (Frontiers in Immunology, 2017)
Glucocorticoids (GCs) have long been known to be immune suppressive and synthetic variants are widely used in the treatment of inflammatory disorders. Here we report that, whilst suppressing the initial production of interferon-γ (IFN-γ), the synthetic GC Dexamenthasone (Dex) enhances the proliferation and survival of NK cells stimulated with interleukin-2 (IL-2) plus IL-12. Inhibition of mTORC1 by rapamycin revealed the immunosuppressive activity of Dex was independent from the effect of enhancing NK cell proliferation. In the presence of IL-2 plus IL-12, Dex also increased the percentage of NK cells that were CD16+ and DNAM1bright, increased the level of expression of CD94 or NKG2A, and improved mitochondrial function of NK cells. Moreover, NK cells treated with cytokines IL-2 and IL-12 plus Dex, followed by a 7-day rest, displayed an increased IFN- γ response upon re-stimulation. Thus, there is a dichotomic effect of GCs on NK cell function dependent on the local cytokine milieu: the NK cell effector response is initially suppressed but, dependent on the cytokines present, Dex can also augment the proliferation, survival and reactivity of human NK cells in a secondary recall response.